Improving the competitiveness of business structures in the conditions of innovative foresight - Bekebayeva, M.O.; Koptayeva, G.P.; Shadieva, A.A.; Turebayeva, Zh.K.; Orazova, B.B. (BUKETOV BUSINESS REVIEW, 2022)
Object: It is important to create favorable conditions for doing business in the conditions of innovative foresight because of difficulties in effective management and formation of competitiveness of enterprises in various fields of activity. Due to the fact that the competitiveness arising in the entrepreneurial structure is not guaranteed by the possession of production factors, as well as other key factors of the organization of entrepreneurial activity, as the existing entrepreneurial talent does not exclude that the organization may have a healthy competitiveness. At the moment, the business structure has an intellectual component of development, which includes the creation and implementation of the latest technologies. To obtain sustainable or exploratory competitive advantages that make up strategic competitiveness, it is necessary to have the ability to develop innovations and support transitions. Methods: Comparative analysis, calculation of relative indicators, deduction and visualization methods, the method of expert assessments. Results: Proposals have been developed for the implementation of the algorithm of the management method and improving the competitiveness of entrepreneurial structures based on innovative foresight, and a number of different issues related to the creation and implementation of a strategy to increase competitiveness have been considered, but due to the incompleteness of the study of the entrepreneurial structure, there are certain problems in the application of the method. Conclusions: An entrepreneurial structure will have a development component in the form of an innovative foresight, that is, include the ability to produce and implement innovations in the management system of an entrepreneurial structure, then this will be a sustainable competitive advantage. The article considers innovative foresight as an effective tool for increasing the competitiveness of business structures in the long term.